2006
DOI: 10.1002/app.25513
|View full text |Cite
|
Sign up to set email alerts
|

Effect of filler content and size on the properties of ethylene vinyl acetate copolymer–wood fiber composites

Abstract: In this study, the main focus was on the effect of wood fiber (WF) content and particle size on the morphology and mechanical, thermal, and water-absorption properties of uncompatibilized and ethylene glycidyl methacrylate copolymer (EGMA) compatibilized ethylene vinyl acetate copolymer-WF composites. For uncompatibilized composites, the tensile strength decreased with increasing WF content, whereas for compatibilized composites, the tensile strength initially decreased, but it increased for composites contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
34
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 23 publications
7
34
0
1
Order By: Relevance
“…6). This is in line with the work done by Dikobe and Luyt [30], and can be explained by the weak interaction between hydrophilic WF and hydrophobic LDPE. It is, however, interesting to see that the presence of nanosilica further reduces the tensile strength of the LDPE/WF/ nano-silica composites.…”
Section: Resultssupporting
confidence: 80%
“…6). This is in line with the work done by Dikobe and Luyt [30], and can be explained by the weak interaction between hydrophilic WF and hydrophobic LDPE. It is, however, interesting to see that the presence of nanosilica further reduces the tensile strength of the LDPE/WF/ nano-silica composites.…”
Section: Resultssupporting
confidence: 80%
“…Work done by Dikobe and Luyt, 27 however, showed that EVA and EGMA do not react with each other. EVA and EGMA are, however, very miscible (according to differential scanning calorimetry curves not presented).…”
Section: Resultsmentioning
confidence: 94%
“…As the particle size in a composite decreases, the filler dis- persion and matrix-filler interaction, although it may be weak, should increase. 35 The increased interaction and interfacial adhesion would result in the higher modulus observed. But this trend was not observed when the fine particles were removed from the filler (entries 8 and 9).…”
Section: Dynamic Mechanical Analysismentioning
confidence: 94%